Pengaruh Kepemimpinan Kepala Sekolah dan Peran Komite Sekolah terhadap Kinerja Guru SMP Negeri di Kecamatan Pangkalan Lampam - Erwin Prabowo; Happy Fitria; Nur Ahyani (Departement of Mathematics Education, 2023)
The purpose of the researchers in conducting this study was to find out and describe the influence of the leadership of the school principal and the role of the school committee together on the performance of teachers of public junior high schools in the District of Pangkalan Lampam. The time for conducting this research was from August to October 2022, and it was carried out at the public middle school in Pangkalan Lampam District, Ogan Komering Ilir Regency. This study employed correlational quantitative research, employing the method after the fact. The sample in this research is made up of 81 participants. From the results of the research, it was found that the influence of the principal's leadership on the performance of state junior high school teachers in Pangkalan Lampam District amounted to 16.1%. The size of the contribution of the influence of the school committee on the performance of state junior high school teachers in Pangkalan Lampam Subdistrict was 8.5%. And the size of the contribution of the influence of the principal's leadership and the role of the school committee together on the performance of state junior high school teachers in Pangkalan Lampam Subdistrict was 21.5%. while the remaining 78.5% is influenced by other factors that are not included in this research.